Impact of Rehabilitation Workouts Using Rubber Bands and Resistance Bands on the Recovery from Ankle Sprain Injuries in Some Team Players in Misan Governorate - Msaed, Majid Mohammed (Indonesian Journal Publisher, 2025)
This paper includes an introduction, significance, methodology, analysis, and conclusions. At the beginning, ankle sprain is introduced, along with the related injuries, causes, and effects. This study is significant as it proposes a rehabilitation method to treat ankle sprain injuries using rubber bands and resistance bands. The statement of the research emphasizes the prevalence of ankle sprain injuries and the corresponding rehabilitation methods using conventional workouts, which may involve loads and might be undesirable, as it causes certain complications. Therefore, this paper aims to design a method to help players and athletes recover from these injuries using rubber bands and resistance bands. Accordingly, the paper hypothesizes that the proposed rehabilitation method effectively treats ankle sprain injuries using rubber bands and resistance bands, with rubber bands being remarkably effective in that respect. Data included ten players with ankle sprain injuries who underwent a recovery using the proposed rehabilitation method from April 20, 2024, to July 1, 2024, at the physiotherapy center in Misan Governorate, Iraq. This study uses an experimental method. Thus, an experimental design encompassing two tentative (equivalent) groups with pretests and post-tests has been designed. Data collection included devices, equipment, measurements, pilot tests, the proposed rehabilitation method, and statistical software. The paper elaborates on research findings by classifying them into tables, graphs, and illustrative figures. Additionally, the paper scientifically analyzes and discusses the results based on previous studies and relevant literature. Finally, the paper develops conclusions, suggestions, and recommendations. Following data analysis and result discussion, the paper developed conclusions that mostly address how the proposed rehabilitation method, which utilizes rubber bands and resistance bands, effectively and positively treats ankle sprain injuries by improving thigh circumference, muscle strength, angles of movement, and degree of pain. Also, the study finds that the proposed rehabilitation method, which utilized rubber bands, is noticeably more effective in the enhancement of muscle strength.